2016
DOI: 10.18632/oncotarget.11955
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-stimulated gene 15 in hepatitis B-related liver diseases

Abstract: This study investigates the association of Interferon-stimulated gene 15 (ISG15) polymorphisms, ISG15 serum levels and expression with HBV-related liver diseases. The ISG15 promoter and the two exons of the gene were screened for polymorphisms in 766 HBV-infected patients and in 223 controls. Soluble ISG15 levels were measured by ELISA. ISG15 mRNA expression was quantified by qRT-PCR in 36 tumor and adjacent non-tumor tissues. The exon 2 allele rs1921A was found associated with decreased progression of HBV-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
3
7
0
1
Order By: Relevance
“…Several IRF5 -modulated genes ( e.g ., ISGs and STATs) involved in the type I IFN signaling pathway are significantly over-expressed in response to viral infection[ 18 ]. This supports the findings of our study, namely that these SNPs may contribute to progression of HBV-related liver diseases through regulating IRF5 expression and subsequent activation of genes in the type I IFN signaling pathway like ISG15 as seen in our study[ 7 ]. Furthermore, although all four studied SNPs were not associated with HCC, the haplotype TCAT contributes to a decreased risk of HCC development in patients with chronic hepatitis B.…”
Section: Discussionsupporting
confidence: 92%
“…Several IRF5 -modulated genes ( e.g ., ISGs and STATs) involved in the type I IFN signaling pathway are significantly over-expressed in response to viral infection[ 18 ]. This supports the findings of our study, namely that these SNPs may contribute to progression of HBV-related liver diseases through regulating IRF5 expression and subsequent activation of genes in the type I IFN signaling pathway like ISG15 as seen in our study[ 7 ]. Furthermore, although all four studied SNPs were not associated with HCC, the haplotype TCAT contributes to a decreased risk of HCC development in patients with chronic hepatitis B.…”
Section: Discussionsupporting
confidence: 92%
“…The interferon signalling pathway constitutes the first‐line defence against viral infections. The role of ISG‐15 in host defence against invading viral pathogens has previously been documented . In fact, our study proves the association of ISG‐15 with treatment response and suggests that the baseline of ISG‐15 expression is associated with treatment prediction.…”
Section: Discussionsupporting
confidence: 76%
“…The role of ISG-15 in host defence against invading viral pathogens has previously been documented. 58 In fact, our study proves the association of ISG-15 with treatment response and suggests that the baseline of ISG-15 expression is associated with treatment prediction. The ISG-15 is correlated with poor in vivo ISG response and poor viral kinetics resulting in poor virological outcomes to standard INFpeg-based therapy in patient infected with HCV.…”
Section: Treatment Type Analysis With the Genes Associated With Hcvsupporting
confidence: 61%
“…A number of enzymes involved in the ISGylation process, namely E3 ligases (HERC5 and EFP/TRIM25) and USP18 have been shown to be associated with cancers via ISGylation-dependent and -independent mechanisms [15][16][17][18]. We have previously shown that ISG15 expression is associated with HBV-related liver diseases, including HCC [23].…”
Section: Discussionmentioning
confidence: 99%